Monetary policy and stock market reaction: developed market and emerging market comparison - Buddi Wibowo (BISMA (Bisnis dan Manajemen), 2021)
This research examines the correlation between monetary policy and stock market reaction. Monetary policy is represented by short term interest rate and exchange rate to USD. This quantitative research uses OLS Regression, SUR, and Panel Regression Method. The results suggest that monetary policy affects the movement of the stock market return. Using OLS and SUR, this study finds that short-term interest rates have a significant negative correlation to return, and exchange rates positively correlate with returning. Using the Panel Data Model, this study finds that short-term interest rates have significant correlations in G7 and emerging countries. Still, the exchange rate is only significant in the emerging market. With SUR, there are common factors that affect the global return to move together. Domestic monetary policy is not an effective tool to influence the stock market because there are common factors in a region. From a financial management perspective, this result gives a practical reason for an investor to create an optimal portfolio through regional stock market diversification. Considering monetary policy in a country as a crucial factor in rebalancing the portfolio, standard regional monetary policy becomes an appropriate strategy.